Genotoxicity of GAL-57 Herbicide in Salmonella typhimurium and Escherichia coli - Dragica Brkić; Slavica Gašić; Adél Vértesi; Vesela Karan; Neško Nešković (Pesticidi i Fitomedicina, 2006)
Genotoxicity of the herbicide GAL-57, containing two active ingredients; bentazon and dicamba, was investigated using the Ames test. Salmonella typhimurium (tester strains TA98 and TA100) and Escherichia coli (strain WP2uvrA) were used. Nine product concentrations were tested at a range of 19.53-5000 μg/plate and each concentration, as well as the controls, in triplicate. Testing was done with and without metabolic activation (liver microsomal fraction, S-9 mix).The results of our investigation revealed no biological or statistically significant increase in mutagenic factors, and this offered a basis for our conclusion that the herbicide GAL-57 has no genotoxic properties (with or without metabolic activation) under experimental conditions in the Ames test.